MeetingCoach: An Intelligent Dashboard for Supporting Effective and Inclusive Meetings - Samrose, Samiha; McDuff, Daniel; Sim, Robert; Suh, Jina; Rowan, Kael; Hernandez, Javier; Rintel, Sean; Moynihan, Kevin; Czerwinski, Mary (CHI 2021, 2021)
Video-conferencing is essential for many companies, but its limitations in conveying social cues can lead to ineffective meetings. We present MeetingCoach, an intelligent post-meeting feedback dashboard that summarizes contextual and behavioral meeting information. Through an exploratory survey (N=120), we identified important signals (e.g., turn taking, sentiment) and used these insights to create a wireframe dashboard. The design was evaluated with in situ participants (N=16) who helped identify the components they would prefer in a post-meeting dashboard. After recording video-conferencing meetings of eight teams over four weeks, we developed an AI system to quantify the meeting features and created personalized dashboards for each participant. Through interviews and surveys (N=23), we found that reviewing the dash-board helped improve attendees’ awareness of meeting dynamics, with implications for improved effectiveness and inclusivity. Based on our findings, we provide suggestions for future feedback system designs of video-conferencing meetings.